Shell model configurations in the 2$_1^+$ state in $^{46}$Ca from a g-factor measurement - Taylor, M.J.; Benczer-Koller, N.; Bernstein, L.; Cooper, J.; Hiles, K.; Judson, D.S.; Kumbartzki, G.; Maier-Komor, P.; McMahan, M.A.; Mertzimekis, T. J.; Phair, L.; Robinson, S.J.Q.; et al. (Phys. Lett. B, 2005)
{The g factor of the first excited 21+ state in 46Ca has been remeasured with better accuracy than previously obtained, g(21+, 46Ca) = -0.26(6). The experiment utilized the transient field technique combined with Coulomb excitation in inverse kinematics. This result was analyzed in terms of shell model plus deformed core calculations. The positive g factors of the 2 1+ states in Ca and Ca suggest that the 21+ state wave functions require significant particle-hole excitations of the Z = 20
Keywords: 46Ca; Coulomb excitation; g factor; Inverse kinematics; Magnetic moment; Transient field